Smart Governance of Urban Ecological Environment Driven by Digital Twin Technology: A Case Study on the Ecological Restoration and Management in S island of Chongqing. Issue 7 (1st November 2022) - Yue, A; Mao, C; Zhao, S
Abstract: China is undergoing rapid urbanization, which has caused undesirable urban sprawl and ecological deterioration. Combining information technology for ecological environment governance is an effective measure to improve governance efficiency. In this paper, based on the analysis of the ecological restoration and governance case of S Island in Chongqing, an ecological intelligent governance system architecture based on the integration of multiple information technologies such as digital twin is extracted. The research shows that the S Island is based on the technical concept of the digital twin, and integrates a variety of information technology integration, collects and processes a large amount of data generated in the whole process of S Island repair and operation, and builds it based on the digital twin concept and accurately maps the physical space. This system model can be stored and processed based on the integrated data, realize knowledge graph visualization, algorithm optimization, and iterative integration for different objects and application scenarios, and finally serve different functional modules in ecological governance, which can be used to support Smart governance of cities.